2021
DOI: 10.2478/amtsb-2021-0002
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Legislative Changes on the Number of Calls to the Romanian Covid 19 Telverde Helpline

Abstract: On 24th of February 2020, the Ministry of Health in Romania announced the operationalization of the Green Line, known as Telverde, within the National Institute of Public Health, in order to provide citizens with information related to the prevention of Sars-Cov-2 infection. The number of registered calls increased considerably at the time of the declaration of the pandemic, the beginning and the cessation of the state of emergency and during the issuance of military ordinances. Different key periods were stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 1 publication
2
3
0
Order By: Relevance
“…Further spikes in contacts coincided with national and regional lockdowns and the introduction of a new helpline in mid 2020. Our findings are consistent with international studies showing helpline service demand increased following lockdowns or spikes in infection rates (22)(23)(24)(25)(26), followed by decreased demand (22)(23)(24)26). Moreover, although there was a gradual 0.5% decline in contacts after the first national lockdown, and we have seen some peaks and troughs during regional lockdowns, the overall demand stabilised at a new, higher level with an overall upward trend.…”
Section: Discussionsupporting
confidence: 91%
See 4 more Smart Citations
“…Further spikes in contacts coincided with national and regional lockdowns and the introduction of a new helpline in mid 2020. Our findings are consistent with international studies showing helpline service demand increased following lockdowns or spikes in infection rates (22)(23)(24)(25)(26), followed by decreased demand (22)(23)(24)26). Moreover, although there was a gradual 0.5% decline in contacts after the first national lockdown, and we have seen some peaks and troughs during regional lockdowns, the overall demand stabilised at a new, higher level with an overall upward trend.…”
Section: Discussionsupporting
confidence: 91%
“…This indication of a new higher level of demand based on longitudinal data is a novel finding, although the gradual increase in demand throughout the study period did not reach significance levels. We note that the increases and decreases in demand were more consistent with observations in Australia (∼8% and 3% respectively) (22) and not the observations from the United States or Romania (∼50% increase) (23,25), albeit the Australian data was youth-related. Notably, it is important to acknowledge that qualitative data has shown that contacts to helplines had been already increasing prior to the COVID-19 pandemic control measures, similar to observations by the longitudinal Australian study (22).…”
Section: Discussionsupporting
confidence: 78%
See 3 more Smart Citations